2008
DOI: 10.1016/j.jpainsymman.2007.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Action Research: Developing a Pediatric Cancer Pain Program in Jordan

Abstract: Children's pain is undertreated worldwide. Using a model of pediatric cancer pain management in Amman, Jordan, the authors demonstrated that an action research approach to pain service development resulted in a sustainable program of pain control. Barriers to care were due more often to health professionals' misconceptions concerning pain and opioid use than to concerns related to cultural, religious, or societal beliefs. Successful implementation of a pain management program requires education, policy develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
51
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 13 publications
3
51
0
4
Order By: Relevance
“…Demonstrations have been found to be an effective way of facilitating clinical teaching of psychomotor and observational skills to nurses [32]. This may however, only be effective if appropriate and user friendly scales are introduced in the setting.…”
Section: Discussionmentioning
confidence: 99%
“…Demonstrations have been found to be an effective way of facilitating clinical teaching of psychomotor and observational skills to nurses [32]. This may however, only be effective if appropriate and user friendly scales are introduced in the setting.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, it was found that fear of drug addiction and its side effects was prevalent among the patients in the unit and this was consistent with results reported in previous studies. 3,14,19,20 One explanation for this may be the lack of knowledge about cancer treatment and its consequences among nurses, therefore little information is passed on to patients.…”
Section: Discussionmentioning
confidence: 99%
“…, Finley et al . ). Importantly, these prior studies have highlighted that inequities exist in the pain‐related care provided to children with cancer, yet very few studies have considered the effectiveness of analgesic therapy for children hospitalised for antineoplastic therapy (Zernikow et al .…”
Section: Introductionmentioning
confidence: 97%